2020
DOI: 10.3390/biom10040509
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Varying Fluorination Patterns on the Thermodynamics and Kinetics of Benzenesulfonamide Binding to Human Carbonic Anhydrase II

Abstract: The fluorination of lead-like compounds is a common tool in medicinal chemistry to alter molecular properties in various ways and with different goals. We herein present a detailed study of the binding of fluorinated benzenesulfonamides to human Carbonic Anhydrase II by complementing macromolecular X-ray crystallographic observations with thermodynamic and kinetic data collected with the novel method of kinITC. Our findings comprise so far unknown alternative binding modes in the crystalline state for some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…the final thermodynamic minimum 203 . These highly relevant data, which are in total contrast with the entire Matulis “intrinsic” theory, were thereafter validated by interesting work from the groups of Klebe 205 , 206 and Whitesides 207–209 , and are supported by our analysis of the hydrophobicity of the CA active site 204 as well as the report of several classes of inhibitors which anchor to zinc-bound hydroxide/water molecule 128 . Whitesides’ group elegantly demonstrated using ITC, crystallography and MD that the differences in binding between homologous sulphonamide ligands stem from changes in the number and organisation of active site localised water molecules rather than (or perhaps in addition to) the release of structured water from the apposed hydrophobic surfaces 207 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…the final thermodynamic minimum 203 . These highly relevant data, which are in total contrast with the entire Matulis “intrinsic” theory, were thereafter validated by interesting work from the groups of Klebe 205 , 206 and Whitesides 207–209 , and are supported by our analysis of the hydrophobicity of the CA active site 204 as well as the report of several classes of inhibitors which anchor to zinc-bound hydroxide/water molecule 128 . Whitesides’ group elegantly demonstrated using ITC, crystallography and MD that the differences in binding between homologous sulphonamide ligands stem from changes in the number and organisation of active site localised water molecules rather than (or perhaps in addition to) the release of structured water from the apposed hydrophobic surfaces 207 .…”
Section: Discussionsupporting
confidence: 55%
“…The values for k on ranged from 0.003 to 31 x 10 6 L À1 M À1 , whereas the k off range was exceedingly low, 0.01-0.05 s À1 . Thus, the inhibitory activity was entirely influenced by the association rate k on as also detailed by the groups of Klebe, Cavalli and Whitesides [203][204][205][206][207][208][209][210] , which depends primarily on hydrophobic effects. That is, another major error in the analysis of Matulis and colleagues is the lack of considering the hydrophobic effects when analysing the kinetics of association of the sulphonamide inhibitor within the active site.…”
Section: Discussionmentioning
confidence: 84%
“…Thus,s kilful introduction of fluorine atoms within benzene sulfonamide CAIs represents au nique means to properly tune the k on/off ligand parameters towards CA isoforms worthy of biomedical consideration. [48,52,53] Ar emarkable application of this strategy was demonstrated by Ilies et al,w ho used as eries of mono-/disubstituted sulfanilamide derivatives 30-40 that were kinetically profiled on both CA II and IX isoforms (Figure 8). [54] As previously observed for compound 20,the insertion of afluorine atom in the meta position of 30 significantly affects the ligand-protein interaction, as shown by lower K I values for 31 against CA II.…”
Section: Fluorinated Sulfonamides As Caismentioning
confidence: 99%
“…[47] These findings were further substantiated by kinITC (a method for obtaining thermodynamic and kinetic data by isothermal titration calorimetry) and high-resolution X-ray crystallographic data (Figure 6). [48] Figure 4. CA II in complex with 16 (magenta;P DB 3BL0) and 17 (gray; PDB 2EU3).…”
Section: Fluorinated Sulfonamides As Caismentioning
confidence: 99%
“…[44] [47] and kinITC data of 15 and fluorinated compounds 19 and 20 bound to CA II. [48] Angewandte Chemie Minireviews 23072 www.angewandte.org Kinetic data revealed that the fluorine atom in 20 induced modest dissociation (k off )a nd large association (k on )v alues, which are highly influenced by the hydration state of the enzyme cavity [47][48][49][50] and by the hydrophobic features of the ligand, [51,52] respectively.Similar to the previous case,astriking example is the ad hoc introduction of fluorine substitutions within the benzothiazole scaffold of 21 for assessment of the DH/DS compensation phenomenon on CA II (Figure 7). [49][50][51] As expected, the binding geometry as well as the free binding energy for 21-26, 28,a nd 29 were found to be relatively unchanged, which was ascribed to the compensation effect of the thermodynamic features of the water molecules surrounding the ligands (Figure 7C,D).…”
Section: Fluorinated Sulfonamides As Caismentioning
confidence: 99%